Hubungan Keterampilan Bertanya Guru dan Motivasi Belajar Matematika Siswa di MTs Negeri 2 Lampung Timur - Septiani, Jenny Artha; Rosyidah, Ummi; Iskandar, Iskandar (Papanda, 2026)
Learning motivation is one of the key factors in the success of mathematics learning. One factor that influences students’ learning motivation is the teacher’s questioning skills during the instructional process. Based on observations and interviews, a gap was identified between teachers’ questioning skills and students’ levels of learning motivation in the classroom. This study aims to analyze the relationship between teachers’ questioning skills and students’ motivation in learning mathematics. This research employed a quantitative approach. The population consisted of all Grade VII students of MTs Negeri 2 East Lampung, totaling 161 students. The sample was Class VII A, comprising 30 students selected through cluster random sampling. The research instruments used were questionnaires measuring students’ learning motivation and teachers’ questioning skills. Data were analyzed using the Pearson product-moment correlation test. The results of the data analysis showed that the calculated correlation coefficient (r_calculated) was 0.705, while the critical value (r_table) was 0.374. Since r_calculated > r_table (0.705 > 0.374), it indicates a significant correlation. Therefore, it can be concluded that there is a significant relationship between teachers’ questioning skills and students’ motivation in learning mathematics in Grade VII of MTs Negeri 2 East Lampung. This relationship suggests that the better the teacher’s questioning skills, the higher the students’ motivation in learning mathematics, and vice versa.